The Evaluation of Stocks of Components for Electronic Devices - Stupak, V. (Elektronika ir Elektrotechnika, 2007)
Electronic devices, which are exposed to restoration during exploitation, are discussed. The system of maintenance with necessary components, used for repair of group of devices, is analyzed. The method of the evaluation of quantitative structure of stocks of a component is offered. At calculation of stocks, the index of expenses is taken into account. It allows choosing a rational set of a component. Two tasks of calculation of stocks are analyzed. The first task is solved with the restrictions of an index of expenses. At the restrictions of an index of sufficiency, the second task is solved. The periodic way of replenishment of stocks is considered. As an index of sufficiency, the probability of sufficiency of stocks is analyzed. As an index of expenses, cost of stocks of a component is considered. At the evaluation of stocks, the developed computer program is used. The example of calculation of stocks of a component is provided in the table. Ill. 2, bibl. 9 (in English; summaries in English, Russian and Lithuanian).